PENINGKATAN PENGETAHUAN MELALUI MEDIA VIDEO STUNDACE (STUNTING DAPAT DI CEGAH) BAGI REMAJA - Muchamad Fachrul Ilham; Tegar Maulana; Elma Fitriya; Siti Afiva Rosiana; Fatmarani; Budi Astyandini (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Stunting is a condition where the length or height is less when compared to age. This condition is measured by length or height minus two standard deviations of the WHO child growth standard median. The quality of adolescent health is the key to preventing stunting. Adolescents need to know stunting to prevent stunting cases in the next generation; knowledge can be increased through suitable media. This study aims to determine the level of knowledge of adolescents about stunting between groups with prior knowledge interventions and after being given educational videos from the health office. This research was conducted in March – December 2022. The research design used in this study was quantitative with a Groups Pretest- Posttest Design approach. The sampling technique was Quasi-Experiment with a population of 170 people with a sample of 85 people using the Random Sampling method taken from students with an even number of absences. Student knowledge. The data analysis technique is used to test the instrument's validity and reliability. The data analysis used was univariate analysis with the characteristics of the respondents at the focus of gender and level of knowledge with the influence of the research focus. Based on the results of the research conducted, it can be concluded that the group with the educational video intervention made by the team was compared to their level of knowledge. There is no low category for posttest results, and the results show the excellent category in 58 respondents at 68.2%. Therefore, it can be concluded that the effectiveness of the team's educational video produced a better level of knowledge in respondents during the posttest.